Urban appropriation strategies. Exploring space-making practices in contemporary european cityscapes. - (:unkn) unknown (transcript, 2018)
In the past years, the transiency of european city-making and dwelling has become increasingly hard to disregard. This urban flux calls for a methodological rethinking for those professionals, social and natural scientists, artists, and activists, with an interest in the processes of remaking and reclaiming urban space. With a practical and empirical emphasis, this anthology brings forth a variety of perspectives on urban appropriation strategies, their relation to public space-making, and their implications for future city development, exploring how ideas and practices of appropriation inform and relate to cultural narratives, politico-historical occasions as well as socio-ecological expressions.
Keywords: Stadtentwicklung; Stadtraum; Öffentlicher Raum; Natur; Straßenraum; Urbanität; Nutzung; Partizipation; Bürgerbeteiligung; Raumbildung; Raumaneignung; Teilhabe; Stadtnatur; Recht auf Stadt; Selbstorganisation; Fallbeispiel